Patients with antiphosholipid syndrome and thrombotic recurrences: A real world observation (the Piedmont cohort study). (April 2016) - Bazzan, M; Vaccarino, A; Stella, S; Sciascia, S; Montaruli, B; Bertero, M T; Carignola, R; Roccatello, D
Background: Patients with antiphospholipid syndrome (APS) often have thrombotic recurrences, sometimes despite appropriate ongoing anticoagulant treatment. Identifying APS vascular patients at high risk for thrombotic recurrences is still an unsolved issue. Objectives: To report the real-life experience of thrombotic recurrences in APS patients included in the Piedmont observational cohort study, and evaluate clinical and laboratory risk factors for thrombotic recurrences. Patients: A multi-centre observational study was performed by enrolling 177 patients with vascular APS (primary APS in 99 subjects (56%)); the median follow-up was five years (range 1–26 years). Results: The observed thrombotic recurrence rate was about 7.5/100 patient years in the first five years after the first thrombotic event. While the first recurrence often occurred (45%) in patients who were not on oral anticoagulant therapy (OAT), the second recurrence mainly occurred despite ongoing OAT (80%). However, due to the real-life observational nature of this study, treatment was based on the treating physician's judgement, and no structured therapeutic protocol was applied. Moreover, compliance with OAT was not available. No differences in antiphospholipid antibodies (aPL) profile were observed between patients with or without thrombotic recurrences, but a high risk aPL profile (Miyakis type 1 and 2a) was present in 96% of our patients, 26% of whom had triple positivity. Diabetes ( p  < 0.01, OR 10), inherited thrombophilia ( p  < 0.0078, OR 4) and OAT withdrawal were independent risk factors for recurrences. Conclusions: With the limit of a real-life observational cohort study, the thrombotic recurrence rate in APS was as high as 7.5/100 patient years in the first five years after the first thrombotic event. OAT discontinuation, diabetes and inherited thrombophilia, when associated with a high-risk aPL profile, are risk factors for thrombotic recurrences.